APPROACHES TO THE DEVELOPMENT OF A LITERARY TRANSLATOR'S LINGUISTIC IDENTITY - Michael Naydan; Mariia Ivanytska; Alla Perminova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article discusses the development of the linguistic identity of a novice literary translator in the course of academic training. The authors claim that teaching literary translation presupposes creating an academic environment conducive to untapping the creative potential of translation students. The paper describes an experiment in which 30 Ukrainian translations of the prologue from Julia Franck's novel "Die Mittagsfrau" executed by young translators were analysed. The outcomes of the research allowed for the identification of translation strategies and typical translation mistakes, and the dependence of translations on the translator's linguistic identity. The study proves the hypothesis that creativity comprises an indispensable component of the translator's personal linguistic identity and can be developed in the course of professional training. This also allows the authors to highlight the factors that influence the formation of the translator's professional competence as well as outline perspectives for further research into think-aloud protocols provided both by experienced and novice translators.